Design and Development Student Entrepreneurship Information System - Siti Mukaromah, (ReTII, 2019)
The Entrepreneurship Course is a compulsory subject that must be taken by all students of the Universitas Pembangunan Nasional "Veteran" Jawa Timur. This is done with the aim that students have an entrepreneurial spirit. But just like any other course, if the semester is finished, the student entrepreneurship container formed during lectures is also finished. For this reason, in order for entrepreneurship to continue until students graduate, an entrepreneurial forum is made for students to alumni. The entrepreneurship container is the Student Entrepreneurship Information System or Sirama. In the following article we will discuss the Sirama system design. The analysis design that will be discussed is Use Case Diagram, Conceptual Data Model (CDM) and Physical Data Model (PDM) and the creation of the entrepreneurial information system. The conclusion of this article is the result of system design and development of Sirama has been completed so that the forum to maintain the entrepreneur spirit of students and alumni of the UPN "Veteran" East Java can be continued. Keyword: sirama, uml, enterpreneurship, college student